2015
DOI: 10.1007/s00414-015-1183-5
|View full text |Cite
|
Sign up to set email alerts
|

A single-tube 27-plex SNP assay for estimating individual ancestry and admixture from three continents

Abstract: A single-tube multiplex assay of a small set of ancestry-informative markers (AIMs) for effectively estimating individual ancestry and admixture is an ideal forensic tool to trace the population origin of an unknown DNA sample. We present a newly developed 27-plex single nucleotide polymorphism (SNP) panel with highly robust and balanced differential power to perfectly assign individuals to African, European, and East Asian ancestries. Evaluating 968 previously described intercontinental AIMs from three HapMap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…In the current study, we developed the novel multiplex systems of 42 AISNPs for bio‐geographical origin predictions of three continental populations based on the MassARRAY iPLEX platform. In previous studies, some researchers mainly detected selected SNP loci by TaqMan SNP Genotyping Assay . Compared to these researches, there were some shortcomings in this study.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In the current study, we developed the novel multiplex systems of 42 AISNPs for bio‐geographical origin predictions of three continental populations based on the MassARRAY iPLEX platform. In previous studies, some researchers mainly detected selected SNP loci by TaqMan SNP Genotyping Assay . Compared to these researches, there were some shortcomings in this study.…”
Section: Resultsmentioning
confidence: 94%
“…Wei et al. estimated admixture levels of four central Asian populations (Tajik, Uyghur, Kirgiz, and Kazak) based on a multiplex AISNPs panel, and they found that these populations showed admixture patterns of East Asian and European ancestries . Besides, the same research team re‐analyzed genetic structure of these four populations based on another AISNPs panel and they observed similar results which revealed these populations displayed East Asian and European admixed ancestries .…”
Section: Resultsmentioning
confidence: 97%
“…Wei et al. showed that the admixture proportions of East Asian and European ancestral populations for Uyghurs in Xinjiang were 46 and 49% based on a 27‐AIM‐SNP analysis, indicating a higher European ancestral component in Uyghur group from Xinjiang. By analyzing 26 Y‐STR genetic markers, Bian et al.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information regarding the overall 16 populations were presented as follows: ESN, Esan in Nigeria ( n = 99); YRI, Yoruba in Ibadan, Nigeria ( n = 108); MSL, Mende in Sierra Leone ( n = 85); GWD, Gambian in Western Division ( n = 113); LWK, Luhya in Webuye, Kenya ( n = 99); TSI, Toscani in Italy ( n = 107); FIN, Finnish in Finland ( n = 99); IBS, Iberian populations in Spain ( n = 107); CEU, Utah residents with Northern and Western European ancestry ( n = 99); GBR, British in England and Scotland ( n = 91); KHV, Kinh in Ho Chi Minh City, Vietnam ( n = 99); CDX, Chinese Dai in Xishuangbanna, China ( n = 93); CHB, Han Chinese in Bejing, China ( n = 103); CHS, Southern Han Chinese, China ( n = 105); JPT, Japanese in Tokyo, Japan ( n = 104); XJU, Uyghurs in Urumchi, China ( n = 517). The other two admixed African populations (ASW, ACB) included in the 1000 Genomes were excluded from the reference dataset for quality control .…”
Section: Methodsmentioning
confidence: 99%
“…To further examine the accuracy, we compared our UT-AIM250 panel and two published panels, 34 AIM-panel [14] (termed Phillips-AIM34) and 278 AIM-panel [39] (termed Wei-AIM278), on the Admixed American (AMR) population also from the 1000 Genomes Project. Those panels were generated from three continental populations (with slightly inclusion criterion and samples available at the time): African (AFR), European (EUR), and East Asian (EAS).…”
Section: Resultsmentioning
confidence: 99%